Sublingual misoprostol versus dinoprostone gel in labour induction - Juveria Jahangir; Fatima Zahra Shaik Mohd (Barpeta Obstetrics and Gynaecological Society, 2020)
Objective: This study was carried out to compare the outcome and safety of intravaginal misoprostol (PGE1) and intra-cervical dinoprostone gel (PGE 2) in induction of labour. Methods: In this study, 100 women between 19 and 30 years of age with a single live fetus, cephalic presentation and full-term pregnancy were included for induction of labour. Fifty women received 50 micrograms of Misoprostol intravaginal (study group) and 50 women received 0.5 mg of intracervical dinoprostone gel (control group). The comparison were made on the average time taken for the start of labour, the induction time at birth, the average duration of delivery, the need for oxytocin, the method of delivery. Results: The average time taken for the onset of labour was lower in the misoprostol group than in the dinoprostone group (40.30 min v/s 1 hour and 35 minutes). Similarly, the induction phase to the active phase (1 hour and 44 min v/s 4 hours and 25 min) and the active phase at the time of administration to delivery ( 3 hours 00 min v / s 4 hours 48 min) was lower for the misoprostol group. The rate of caesarean section was lower in the misoprostol group (6% v / s 26%). Maternal side effects were negligible in both groups and the neonatal outcome was good in both groups. The cost of induction was much lower in the misoprostol group. Conclusion: Misoprostol is a safe, effective and economical drug, suitable for the mother and the fetus for the induction of labour.